Diagnostic precision of the Wisconsin Card Sorting Test in assessing cognitive deficits in substance use disorders. Issue 2 (4th March 2021) - Faustino, B.; Oliveira, J.; Lopes, P.
Abstract: The Wisconsin Card Sorting Test (WCST) is a widely used neuropsychological instrument to assess executive functions related to cognitive flexibility and abstract reasoning. However, there is a lack of studies investigating the diagnostic precision of this instrument in substance use disorders. In this study, we aimed at assessing the sensitivity and specificity of the WCST in discriminating the performance of participants with substance use disorder with cognitive deficits and participants from the general population without cognitive deficits. The sample comprised three groups of participants with substance use disorders (opioid use disorder in harm reduction with methadone maintenance; opioid use disorder in treatment in a therapeutic community; alcohol use disorder in a therapeutic community) and a normative group of healthy adults. The total sample consisted of 587 participants that were assessed with cognitive tests for executive functions, general cognitive functioning, and self-reported depression. The results showed differences between groups in most WCST variables, providing evidence of discriminant validity for this test. Convergent validity was also established by weak to moderate correlations with general cognitive functioning. Cutoff points based on receiver operating characteristic (ROC) curves were calculated for the WCST variables. Overall, the WCST was sensitive to changes in cognitive flexibility and abstract reasoning that are key features of substance use disorders.